Wheat supplement with buckwheat affect gut microbiome composition and circulate short-chain fatty acids - Yao, Di; Yu, Qiaoru; Xu, Lei; Su, Tingting; Ma, Lixue; Wang, Xiaoyu; Wu, Mengna; Li, Zhijiang; Zhang, Dongjie; Wang, Changyuan (Frontiers in Nutrition, 2022)
Buckwheat has beneficial effects on human intestinal health, which is often compounded with wheat to make food. Therefore, the effect of cereals mixture via in vitro fermentation on gut microbes and short-chain fatty acids (SCFAs) were investigated in this study. The mixture of wheat and tartary buckwheat (WT) produced more lactate and acetate, and the mixture of wheat and sweet buckwheat (WE) produced more propionate and butyrate. Compared with wheat (WA), the relative abundance of some beneficial bacteria significantly increased, such as Sutterella in WT and Faecalibacterium in WE. Cereals mixture also affected the expression of functional genes, involved in metabolic pathways and carbohydrate-active enzymes (CAZymes) that modulated SCFAs generation. This study provides new insights into the effects of sweet and tartary buckwheat on intestinal function, which is beneficial to applying both types of buckwheat in practical.